Adolescent Women with Experience of Dating Violence: Self-compassion and Posttraumatic Growth - Nabilah, Vikha Alya; Kusristanti, Chandradewi (UI Scholars Hub, 2021)
The most frequently reported cases of violence in Indonesia are against women, and the second highest are dating violence. Similar to other traumatic events, violence leads to negative impacts. Conversely, previous research suggests that trauma survivors might experience positive changes, that is, posttraumatic growth (PTG). In fact, this study aims to determine self-compassion’s contribution to PTG among Indonesian adolescent women who have experienced dating violence; to ensure that all participants had experienced dating violence, we used the trauma and life events (TALE) checklist for screening. Self-compassion helps trauma survivors increase positive thoughts and seek meaning. Therefore, in this study, we argue that self-compassion augments PTG. The study is quantitative, with three questionnaires used: self-compassion scale-short form to measure self-compassion (α = .759), posttraumatic growth inventory-short form to measure posttraumatic growth (α = .643) and trauma and life events checklist as the screening tool to ensure participants had experienced a traumatic event. A simple regression test revealed that among participants (n = 306), self-compassion significantly contributed to PTG by 12% (p = .000, R2 = .120). These findings can be used as a reference in establishing preventive programs or interventions to improve self-compassion and increase awareness about healthy relationships, especially among adolescents.